1975
DOI: 10.1159/000245583
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C Supplementation of Old People with Low Blood Levels

Abstract: Ascorbic acid blood levels were estimated in 828 elderly people living in the community. 297 subjects with low blood levels were admitted to a 2-year controlled trial of vitamin C. Despite a rise in plasma and leucocyte levels, vitamin C produced no apparent benefit in terms of mortality, morbidity or mental senescence. On following up all those who were originally seen, it was found that a higher proportion of deaths occurred among subjects whose leucocyte levels were below 15 μg/l08 cells than among the rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…'I'hc interpretation of those two trials is complicated by the fact that the follow-up was relatively short and that they wcrc carried out in subjects with poor nutritional status drawn from a population with low rates of coronary heart disease and a haciiiorrhagic stroke pattern. Also two sinall trials of short duration [56,57] have bccn reported. In one trial 538 elderly patients wcrc allocated randoiiily to be administcrcd cithcr 200 ing vitamin C per day o r placebo.…”
Section: Discussionmentioning
confidence: 99%
“…'I'hc interpretation of those two trials is complicated by the fact that the follow-up was relatively short and that they wcrc carried out in subjects with poor nutritional status drawn from a population with low rates of coronary heart disease and a haciiiorrhagic stroke pattern. Also two sinall trials of short duration [56,57] have bccn reported. In one trial 538 elderly patients wcrc allocated randoiiily to be administcrcd cithcr 200 ing vitamin C per day o r placebo.…”
Section: Discussionmentioning
confidence: 99%
“…Ascorbic acid levels also decline in the tissues of aging rats, even though the rat does not depend on an external source of ascorbic acid (123). However, generous doses of ascorbic acid given daily for lengthy periods failed to improve the clinical condition of nursing-home patients (6,21) or resulted at best in small increases in body weight and in plasma protein levels (139). This implies that total intake was probably over 100 mg ascorbic acid daily.…”
Section: Vitamin Cmentioning
confidence: 99%